PENGEMBANGAN MEDIA PEMBELAJARAN PEMAHAMAN SINTAK MODEL PEMBELAJARAN ABAD 21 BERBASIS MOBILE (JRFES (Jurnal Riset Fisika Edukasi dan Sains), 2021)
This research aims to develop a learning medium of understanding the intake of a valid and practical mobile-based 21st-century learning model. The urgent problem in this study is the lack of understanding of students' learning materials in the 21st century as well as the lack of learning media in understanding the material. This research is a research development or R&D (Research and Development) that aims to describe the process of Developing Mobile-Based Learning Media that is valid and practical. The development design used is the instructional development institute (IDI) model. The subject of this study consisted of 6 expert validator of materials and media. 2 responses of lecturers and students of the class of 2017 Informatics Study Program which amounted to 49 people. The research was conducted at STKIP PGRI West Sumatra. The results showed that the validity test value by material experts obtained a value of 0.868 with a valid category and for validity test results by media experts get a value of 0.812 valid categories. Practicality test results by lecturers obtained a percentage of the value of 88% with a very practical category and also seen from the practicality test students get a percentage of the value of 90.7% with a very practical category. Based on the data, it can be concluded that the Learning Media understanding Sintak Mobile-based 21st Century Learning Model developed is quite valid and practical.